2021
DOI: 10.1007/s10198-021-01396-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost–utility analysis of risk-reducing strategies to prevent breast and ovarian cancer in BRCA-mutation carriers in Switzerland

Abstract: Objective We aimed to identify the most cost-effective of all prophylactic measures available in Switzerland for women not yet affected by breast and ovarian cancer who tested positive for a BRCA1/2 mutation. Methods Prophylactic bilateral mastectomy (PBM), salpingo-oophorectomy (PBSO), combined PBM&PBSO and chemoprevention (CP) initiated at age 40 years were compared with intensified surveillance (IS). A Markov model with a life-long time horizon was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 98 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…For BRCA1 PV carriers, two studies found that RRSO at the age of 35 was the most cost-saving [ 28 ] or cost-effective, with an ICUR of $2101/QALY [ 29 ], compared to other surgical prevention strategies (RRM or combined RRM and RRSO), chemoprevention (tamoxifen/oral contraceptives) and surveillance. Three other studies found that combined RRM and RRSO at the age of 40 [ 41 ], or combined RRM at the age of 35 with RRSO at the age of 45 [ 53 ] was the most cost-saving; RRM at the age of 30 with RRSO at the age of 35 was the most cost-effective, with an ICER of $835/LYG [ 47 ]. For BRCA2 PV carriers, two studies found that combined RRM and RRSO at the age of 35 was the most cost-effective, with an ICUR of $3125/QALY [ 28 ], ant that combined RRM and RRSO at the age of 40 was the most cost-saving [ 41 ], compared with other preventive strategies or surveillance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For BRCA1 PV carriers, two studies found that RRSO at the age of 35 was the most cost-saving [ 28 ] or cost-effective, with an ICUR of $2101/QALY [ 29 ], compared to other surgical prevention strategies (RRM or combined RRM and RRSO), chemoprevention (tamoxifen/oral contraceptives) and surveillance. Three other studies found that combined RRM and RRSO at the age of 40 [ 41 ], or combined RRM at the age of 35 with RRSO at the age of 45 [ 53 ] was the most cost-saving; RRM at the age of 30 with RRSO at the age of 35 was the most cost-effective, with an ICER of $835/LYG [ 47 ]. For BRCA2 PV carriers, two studies found that combined RRM and RRSO at the age of 35 was the most cost-effective, with an ICUR of $3125/QALY [ 28 ], ant that combined RRM and RRSO at the age of 40 was the most cost-saving [ 41 ], compared with other preventive strategies or surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…Three other studies found that combined RRM and RRSO at the age of 40 [ 41 ], or combined RRM at the age of 35 with RRSO at the age of 45 [ 53 ] was the most cost-saving; RRM at the age of 30 with RRSO at the age of 35 was the most cost-effective, with an ICER of $835/LYG [ 47 ]. For BRCA2 PV carriers, two studies found that combined RRM and RRSO at the age of 35 was the most cost-effective, with an ICUR of $3125/QALY [ 28 ], ant that combined RRM and RRSO at the age of 40 was the most cost-saving [ 41 ], compared with other preventive strategies or surveillance. A study reported that RRSO at the age of 40 was the most cost-effective, with an ICUR of $5535/QALY [ 29 ], and another one found that RRM at the age of 35 was the most cost-saving [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRCA1 gene mutations cause familial breast-ovarian cancer-1 (BROVCA1), and BRCA2 gene mutations cause familial breast-ovarian cancer-2 (BROVCA2). Up until the age of 80, women who are BROVCA1-sensitive have a cumulative risk of 72% for breast cancer and 44% for ovarian cancer [ 8 , 9 , 10 ]. However, BROVCA2-sensitive women have a cumulative risk of 17% for ovarian cancer and 69% for breast cancer at the same age [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up until the age of 80, women who are BROVCA1-sensitive have a cumulative risk of 72% for breast cancer and 44% for ovarian cancer [ 8 , 9 , 10 ]. However, BROVCA2-sensitive women have a cumulative risk of 17% for ovarian cancer and 69% for breast cancer at the same age [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%